Solidification of Worldview, Liberation Strategy and Revival of Sunnism Leading to the 12th Century A.D. / 6th Century A.H. Muslim Liberation of Jerusalem - Mohd Amin, Muhammad Husni (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This study examines the phenomena leading to the Muslim liberation of Jerusalem in 1187 A.D., namely: (1) solidification of Sunni worldview, (2) liberation strategy, and (3) revival of Sunnism. The study refers to the framework of Syed Muhammad Naquib al-Attas, a contemporary proponent of the Sunni-Sufi metaphysical system chiefly represented by metaphysicians of the focus milieu. The study uses textual analysis to explain the undermining of the Sunni worldview and its later solidification. The historiography method is used by adopting liberally the approaches of A. R. Azzam, Majid ʿIrsan al-Kaylani, and Ali M. Sallâbi to explain the phenomena of Sunni revival and liberation strategy, focusing on the rise of notable figures and operationalisation which contributed to the efforts through the establishment of important centres of learning acting as catalysts for intellectual and spiritual development in the milieu, all of which explain Muslim survival in the wake of Crusader invasion, recovery, and success of the 1187 counterattack.